Solid-pseudopapillary neoplasm of the pancreas: Clinicopathologic and immunohistochemical analysis of nine cases - Banu Yilmaz Ozguven; Deniz Tuncel; Nedim Polat; Damlanur Sakiz; Fevziye Kabukcuoglu; Hakan Koksal; Huseyin Kaya (Wolters Kluwer Medknow Publications, 2015)
Background: Solid-pseudopapillary neoplasm (SPPN) of the pancreas is a distinctive tumor of low malignant potential with a predilection for female patients in the second and third decades of life. We studied nine cases of SPPN of the pancreas and reviewed the literature concerning these uncommon tumors. Materials and Methods: A total of 7 cases of SPPN located in the tail of the pancreas and two located in the head of the pancreas were presented. Distal pancreatectomy in three patients and distal pancreatectomy with splenectomy in two patients Whipple's operation in four patients were performed. Histological diagnosis was made by performing hematoxylin-eosin and periodic acid-Schiff staining, immunohistochemical staining. Follow-up of the patients was between 2 months and 12 years. Results: Computed tomography and magnetic resonance imaging were found as equivocal for diagnosis. Mass containing cystic and solid areas were not characteristic but raised suspicion of SPPN. Pathologic examination showed SPPN in all patients. No metastasis or recurrence was detected during follow-up. Conclusions: Solid-pseudopapillary neoplasm is a relatively rare tumor, and patients tend to survive for a long period. Preoperative imaging is not characteristic. Pathologic examination is the mainstay in the diagnosis. Complete surgical removal is the best choice of treatment.